Risk factors for bovine paratuberculosis I. The univariate analysis of risk ractors for bovine paratuberculosis - Çetinkaya, Burhan; Erdo?an, Hidayet M.; Morgan, Kenton L. (Scientific and Technical Research Council of Turkey, 1997)
Data collected by a postal questionnaire sent to 3772 randomly-selected dairy farmers in England and the border regions in Wales were used to estimate the univariate relationships between the presence of clinical paratuberculosis and farm and management factors associated with that disease. Eight variables were determined to be risk factors for clinical disease. These were calving place, group size of the calves, the length of keeping calves in the groups, type of concentrate feeds to calves, breed, source of replacements, the presence of farmed deer and region. Since paratuberculosis is predominantly subclinical, these contributing factors may play important roles in switching subclinical infection to overt disease.
Keywords: Cattle; Farm and management variables; Paratuberculosis; Univariate analysis